Autoimmune disease and aesthetic medicine: a holistic approach - Górska, Magdalena; Kmak, Bożena; Szot, Anna (Quality in Sport, 2024)
Introduction and purpose The field of aesthetic medicine has experienced rapid advancement in recent years. It serves primarily aesthetic purposes while also supporting various medical treatments. The range of available aesthetic medicine procedures continues to expand, with numerous studies confirming their therapeutic efficacy in treating certain diseases or conditions. Conversely, a substantial list of contraindications exists, particularly in autoimmune diseases, necessitating caution and precluding the performance of certain aesthetic treatments. Autoimmune diseases entail the body’s immune system attacking its tissues, a process whose complete development and maintenance in specific diseases remains incompletely understood. Injection treatments like hyaluronic acid and mesotherapy have demonstrated considerable promise in aiding individuals with autoimmune connective tissue diseases to lead everyday lives. This study discusses to what extent selective aesthetic medical procedures could be safely performed in patients with the most common autoimmune diseases. Material and methods A literature review was conducted through an extensive bibliographic search, primarily focusing on original research articles from reputable databases such as PubMed, BioMed Central, Polish Medical Platform, and Google Scholar. The search was specifically targeted towards articles discussing particular autoimmune diseases and specific aesthetic procedures. Conclusion Established relationships between autoimmune diseases and specific aesthetic medicine treatments have been identified, highlighting their ineffectiveness or inadvisability. In such instances, the physician’s extensive knowledge and the necessity for a comprehensive, individually tailored assessment before the procedure often dictate a patient’s exclusion from specific therapies.